Sex differences in post-traumatic stress disorder in a high adversity cohort of South African adolescents: an examination of depressive symptoms, age, and trauma type as explanatory factors. Issue 1 (1st January 2021) - Hiscox, Lucy V.; Hiller, Rachel; Fraser, Abigail; Rabie, Stephan; Stewart, Jackie; Seedat, Soraya; Tomlinson, Mark; Halligan, Sarah L.
ABSTRACT: Background: Evidence from high-income countries (HICs) has documented a higher rate of post-traumatic stress disorder (PTSD) in females than males. However, data are limited on sex differences in PTSD from low- and middle-income countries (LMICs), despite particularly high levels of trauma experienced by LMIC youth. Objectives: In a sample of adolescents from an impoverished South African community, we examined sex differences in PTSD, as well as co-occurring depression, adolescent age, and the type and extent of trauma exposure as potential contributors to female vulnerability. Methods: Participants were recruited from high schools in the Khayelitsha area of Cape Town. Self-reported trauma exposure, PTSD and depressive symptoms were measured in 797 adolescents (62% female) aged 13–17 years. Poisson regressions were used to examine Risk Ratios (RR) based on probable PTSD diagnoses, and linear regressions were applied to assess posttraumatic stress symptom (PTSS) severity. Results: 92% of adolescents reported trauma exposure, of whom 28% had probable PTSD. Prevalence of PTSD was higher for females than for males, even when controlling for total trauma exposure (RR = 1.71, p < .001) and co-occurring depressive symptoms (RR = 1.45, p = .005). By contrast, sex differences in depression were eliminated after controlling for co-occurring PTSS. There was little evidence of age effects on the emergence of sex differences. At lower thresholds of interpersonal trauma, females showed higher levels of PTSS compared to males, but no sex differences were found at high levels of exposure. Conclusion: Higher PTSD rates are observed in adolescent females in a high adversity-LMIC sample suggesting sex differences are robust across international contexts. Sex differences in PTSD are unlikely to be explained by co-occurring depression and in this context sex differences in depression may be secondary to trauma and PTSD. However, exposure to significant interpersonal trauma appears to overrule any specific female vulnerability. HIGHLIGHTS: Sex differences in post-traumatic stress disorder are observed in adolescence from a high-adversity LMIC. Greater female risk occurs even when adjusting for trauma exposure and depressive symptoms. Females also show greater vulnerability to lower thresholds of interpersonal trauma.